Analisis Drainasi di Saluran Cakung Lama Akibat Hujan Maksimum Tahun 2013 dan 2014 - Puji Harsanto; Surya Budi Lesmana; Sherly Devianty (Universitas Muhammadiyah Yogyakarta, 2014)
Flooding is an annual disaster for Indonesia. Jakarta is a city that each year nearly always experienced by flooding. The rapid development made the impervious area dropped drastically. Micro drainage is not capable of passing the volume of direct runoff. It makes many regions in Jakarta experienced by floodwaters. The aim of this research is to analyze the micro drainage capacity in Cakung Lama River. Simulations are performed with HEC-RAS 1D. The flood data is maximum rainfall on 2013 and 2014. Two scenarios normalization is done for reducing the inundated area around the river. Based on the simulation results, the existing conditions are not able to accommodate the discharge due to maximum rainfall 2013 dan 2014. Normalization of the river will give good results if the width of the river 5 m and the depth of the river is 3 m.